Scientific Writing Series: Case-Control studies - Quispe, Antonio M. (2020)
Introduction: A case-control study is a study comparing individuals who had an outcome of interest (cases) versus individuals who had no such outcome (controls) with respect to the exposure of interest, potentially a "risk factor "or" protection factor." The objective of a case-control study is primarily to determine if there is an association between one exposure (or several) and an outcome of interest. This association must be quantified and reported as an odds ratio or odds ratio taking into account its strengths and limitations. In general, this type of study offers as advantages its relatively low cost and speed with which it is possible to carry them out. However, they are not ideal if what you want to investigate are frequent outcomes or with long latency periods. In this article, the primary methodological considerations of the design of case-control studies have been reviewed, hoping thereby to contribute to promoting their correct use and interpretation.